1984
DOI: 10.1002/hep.1840040201
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Morphological Alterations of Baboon Hepatic Mitochondria After Chronic Ethanol Consumption

Abstract: Baboons fed ethanol (50% of total calories) chronically develop ultrastructural alterations of hepatic mitochondria. To determine whether mitochondrial functions are also altered, mitochondria were isolated from nine baboons fed ethanol chronically and their pair-fed controls. At the fatty liver stage, ADP-stimulated respiration was depressed in ethanol-fed baboons by 59.4% with glutamate, 43.2% with acetaldehyde, 45.1% with succinate and 51.1% with ascorbate as substrates. A similar decrease was noted in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0
1

Year Published

1984
1984
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(47 citation statements)
references
References 45 publications
5
41
0
1
Order By: Relevance
“…Evidence for injury was provided by alteration in mitochondrial redox state (see above) and the release Of enzymes from the liver, in particular the mitochondrial enzyme GDH (Table IV), the output of which was strikingly increased in the alcohol-fed animals. Release of this mitochondrial enzyme can be interpreted as evidence for mitochondrial injury, which is consistent with our previous studies that revealed striking biochemical and morphologic alterations of the mitochondria in similarly treated baboons (9); The mechanism for the mitochondrial injury has not been fully elucidated and different processes may be involved in the various toxic manifestations recorded in the present study; one of the factors is probably acetaldehyde, the toxicity of which has been reviewed elsewhere (3,48). Electronmicroscopic studies of liver mitochondria in alcoholics have revealed striking morphologic alterations, including swelling and abnormal cristae.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Evidence for injury was provided by alteration in mitochondrial redox state (see above) and the release Of enzymes from the liver, in particular the mitochondrial enzyme GDH (Table IV), the output of which was strikingly increased in the alcohol-fed animals. Release of this mitochondrial enzyme can be interpreted as evidence for mitochondrial injury, which is consistent with our previous studies that revealed striking biochemical and morphologic alterations of the mitochondria in similarly treated baboons (9); The mechanism for the mitochondrial injury has not been fully elucidated and different processes may be involved in the various toxic manifestations recorded in the present study; one of the factors is probably acetaldehyde, the toxicity of which has been reviewed elsewhere (3,48). Electronmicroscopic studies of liver mitochondria in alcoholics have revealed striking morphologic alterations, including swelling and abnormal cristae.…”
Section: Discussionsupporting
confidence: 91%
“…Two pediatric peritoneoscopes (Olympus Co., Tokyo, Japan) were introduced in the abdominal cavity (using the standard procedure) for spectrophotometric measurements (through optic fibers) and for insertion of a hydrogen electrode under the liver capsule. Reflectance spectroscopy was not carried out in all animals because in some, the liver surface could not be visualized, due to adhesions secondary to prior surgery, carried out to obtain surgical liver biopsies (9). After the start of the alcohol infusion, ketamine was not required any more.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the activity of the mitochondrial respiratory chain could be responsible for both diminished b-oxidation and citric acid cycle activities. Many studies have found diminished respiratory chain activity in alcoholic fatty liver in both rat [33,34] and baboon [35], and these have been attributed to lowered transcription of mitochondrially encoded subunits of respiratory chain proteins [36]. The only human study of the activity of respiratory chain complexes in alcoholic fatty liver, however, found unchanged activity of complex IV, which is partially mitochondrially encoded, when compared with complex II, which is entirely nuclearly encoded [37], suggesting that rat studies may not necessarily be relevant to human alcoholic fatty liver.…”
Section: Impaired B-oxidation As a Cause Of Alcoholic Steatosismentioning
confidence: 99%
“…However, because of continued alcohol intake, other factors become operative, which lead to continued accumulation of triacylglycerol and hence steatosis. In this second phase, there are increases in phosphatidate phosphohydrolase and diacylglycerol acyltransferase activities [15,16], increased fatty acid binding protein levels [19], decreased VLDL secretion [8] and decreased b-oxidation resulting from mitochondrial alterations [33,35,36,38]. In addition, heterozygotes for genetic conditions that would lead to steatosis, such as trifunctional protein deficiency in which heterozygote effects have been observed [43,44], could be predisposed to the development of alcoholic fatty liver.…”
Section: Hypothesismentioning
confidence: 99%